Exploring the promising impacts of naringin and its aglycone constituent naringenin as major citrus flavonoids on diabetes and its complications - Soroush Fotouhi; Aida Yavari; Amir Reza Bagheri; Vahid Reza Askari; Yazdan Gholami; Vafa Baradaran Rahimi (Journal of Functional Foods, 2025)
Due to their capacity to fight apoptosis, inflammation, and oxidative stress, naringin and its aglycone naringenin are considered valuable therapeutic agents for diabetes mellitus (DM). By examining clinical, in vitro, and in vivo studies found from inception until July 2024 on major electronic databases, we explored the pharmacological activities of naringin and naringenin in treating DM and associated risks. Naringin and naringenin improved insulin sensitivity, glucose metabolism, and insulin resistance by activating glucose transporter (GLUT)-4, and peroxisome proliferator-activated receptor (PPAR)-γ. They also possessed antioxidant and anti-inflammatory impacts through regulating mitogen-activated protein kinases (MAPK), nuclear factor kappa B (NF-κB), and Nrf2 signaling pathways. The obtained data emphasizes their role in protecting against heart, neuropathy, nephropathy, gastrointestinal tract, testicles, and skin diabetic complications. Naringin and naringenin could be developed as novel therapeutic options for treating DM, and the knowledge acquired from this review could be a valuable tool for future research projects.